Challenges of Learning English Vocabulary - Kaphle, Keshav Raj (Janaprakash Journal of Multidisciplinary Research, 2024)
This study explored the challenges and strategies of learning vocabulary in the context of English language education. It employed a phenomenological research design. To collect primary data, the researcher used 10 open-ended questionnaires to investigate the learners’ and teachers’ challenges towards vocabulary learning and teaching. It involved 16 students and 3 English teachers from a Nepali educational institution i.e. Janajyoti Campus Bhimad, Tanahun. The fi ndings highlighted various experiences among students, with some fi nding vocabulary acquisition challenging, while others effectively utilized multiple resources and techniques for learning new vocabulary. Pronunciation, spelling, grammar, and memorization emerged as prominent challenges, alongside the importance of peer and teacher support. The study highlighted the signifi cance of employing multiple learning strategies to improve vocabulary skills and overall language profi ciency and recommended promoting collaborative learning environments and developing intrinsic motivation among learners. Overall, the research emphasized the importance of systematic instructional approaches for learners’ diverse needs and preferences in English language education. Ultimately, the study offered comprehensive insights into the dynamic nature of vocabulary acquisition and stressed the necessity of structured instructional approaches tailored to English language learners’ multifaceted needs and preferences.